Ireland : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that Ireland enjoyed strong growth in 2014, at about 5 percent year over year, led by exports and investment. Solid job creation has brought the unemployment rate down to 10.5 percent, from a peak of 15 percent three years ago. These positive economic developments drove higher than expected growth in revenues, helping bring the fiscal deficit down to an estimated 3.9 percent of GDP in 2014 despite some spending overruns. Looking to 2015, Ireland's growth is expected to remain robust, at about 3.5 percent, bolstered by the European Central Bank's quantitative easing. Consumption is beginning to support activity, aided by the impact of falling energy prices on real incomes.